The Role of Social Media in Increasing Umkm Sales in the Digital Era of Deli Serdang Regency - Manurung, Lambok; Widodo, Slamet; Ningsi, Etty Harya (Sinergi International Journal of Management and Business, 2025)
This study aims to analyze the role of social media in increasing sales of Micro, Small, and Medium Enterprises (MSMEs) in Deli Serdang Regency in the digital era. This study uses a quantitative approach with a survey method of 30 MSME actors who actively use social media as a means of promotion. The research instrument is a questionnaire that measures the frequency of social media use, the type of platform used, the level of interaction with customers, and its impact on sales. The results of a simple linear regression analysis show that the use of social media significantly affects the increase in MSME sales (R² = 0.72; p <0.01). These findings indicate that social media such as Instagram, TikTok, and Facebook play an important role in expanding market reach, creating brand awareness, and increasing consumer engagement. This study recommends the need for continuous digital literacy training and collaboration between local governments and social media platforms to optimally support the digital transformation of MSMEs.